Sistem Kepercayaan dan Peran Perempuan Terhadap Pengelolaan Sumberdaya Hutan di Luwu Timur - Jumardi Lanta; Pawennari Hijjang; Safriadi Safriadi (ETNOSIA : Jurnal Etnografi Indonesia, 2019)
This article aims to (1) describe the local community belief system in preserving the forest so that the forest, (2) analyze the factors that influence the local community to convert forest functions (3) Analyze the role of women in preserving forest resources. The research method is a qualitative method with in-depth interview and observation data collection techniques and use PRA (Participatory Rural Appraisal). The results of the study show that there is a well-preserved community belief system known as "metompa/metabe" that is able to prevent people from carrying out massive deforestation at the research site. Likewise the existence of efforts to empower women to manage, maintain and preserve forest resources is an important aspect for women to increase their household income while protecting the forest from damage and extinction.